2016
DOI: 10.1186/s13024-016-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress leads to impaired spatial learning and memory in middle-aged ApoE4-TR mice

Abstract: BackgroundApolipoprotein E (ApoE) is a major lipid carrier that supports lipid transport and injury repair in the brain. The APOE ε4 allele is associated with depression, mild cognitive impairment (MCI) and dementia; however, the precise molecular mechanism through which ApoE4 influences the risk of disease development remains unknown. To address this gap in knowledge, we investigated the potential effects of chronic unpredictable mild stress (CUMS) on ApoE3 and ApoE4 target replacement (ApoE3-TR and ApoE4-TR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…3A, E; P , 0.001). In addition, lower levels of ApoE4, as compared to those of ApoE3, have been reported in the brains of young and aged human ApoE4-TR mice (5,29) and probably in aged nondemented APOE4 carriers (30). Indeed, our Western blot analysis revealed that huApoE levels are lower in the hippocampus of ApoE4-TR mice as compared with ApoE3-TR mice (Fig.…”
Section: Resultsmentioning
confidence: 46%
“…3A, E; P , 0.001). In addition, lower levels of ApoE4, as compared to those of ApoE3, have been reported in the brains of young and aged human ApoE4-TR mice (5,29) and probably in aged nondemented APOE4 carriers (30). Indeed, our Western blot analysis revealed that huApoE levels are lower in the hippocampus of ApoE4-TR mice as compared with ApoE3-TR mice (Fig.…”
Section: Resultsmentioning
confidence: 46%
“…Chronic stress has been identified as a risk factor for AD and has been utilized in pre-clinical studies to induce AD (Leonard 2017;Lin et al 2016;McEwen 2005;Piirainen et al 2017). Rinwa and Kumar used a 28-day chronic stress paradigm made up of random patterns of mild stressors.…”
Section: Studies Of Aging Induced By Environmental Factorsmentioning
confidence: 99%
“…These alterations may render APOE ε4 carriers more susceptible to AD-related pathology and predict conversion to AD in individuals with mild cognitive impairment (MCI) [ 18 , 19 ]. Studies of APOE ε4-targeted replacement mice proposed a clear link between early-life stress and cognitive impairment in middle-aged mice, but whether these observations are of relevance to humans needs to be confirmed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%